Effect of Diagnosis on Outcomes in the Setting of Enhanced Recovery Protocols. Issue 7 (July 2018) - Ban, Kristen A.; Berian, Julia R.; Liu, Jason B.; Ko, Clifford Y.; Feldman, Liane S.; Thacker, Julie K. M.
Abstract : BACKGROUND : Implementation of enhanced recovery protocols in colectomy reduces length of stay and morbidity, but it remains unknown whether benefits vary by clinical diagnosis. OBJECTIVE: Outcomes after colectomy in the setting of enhanced recovery protocols were compared for 3 diagnoses: 1) neoplasm, 2) diverticulitis, and 3) IBD. DESIGN: This was a retrospective registry-based cohort study. SETTINGS: Novel enhanced recovery variables were released in the American College of Surgeons National Surgical Quality Improvement Program in 2014. PATIENTS: Patients with enhanced recovery variable data undergoing elective colectomy (July 2014 to December 2015) for neoplasm, diverticulitis, or IBD were included. MAIN OUTCOME MEASURES: The primary outcome of interest was prolonged length of stay. Additional outcomes included surgical site infection, death/serious morbidity, reoperation, readmission, and days to achieve per os pain control, tolerance of a diet, and return of bowel function. RESULTS: We identified 4620 patients with neoplasm, 1730 patients with diverticulitis, and 593 patients with IBD. Patients undergoing colectomy for IBD were more likely to have prolonged length of stay (OR, 1.98; 95% CI, 1.46–2.69), death/serious morbidity (OR, 1.62; 95% CI, 1.13–2.32), and readmission (OR, 1.54; 95% CI, 1.15–2.08) compared with patients with neoplasm. Patients with IBD took longer than patients with neoplasm or diverticulitis to achieve per os pain control (mean, 4.2 days vs 3.4 and 3.5 days, p < 0.001) and tolerate a diet (mean, 4.1 days vs 3.7 and 3.5 days, p < 0.001). No statistically significant differences in outcomes between patients with neoplasm and diverticulitis were seen. LIMITATIONS: There may be heterogeneity among implemented enhanced recovery protocols. CONCLUSIONS: Patients undergoing colectomy for neoplasm and diverticulitis have improved outcomes in comparison with patients undergoing colectomy for IBD. Knowledge of expected outcomes for patients with different diagnoses may inform clinician and patient expectations. SeeVideo Abstract athttp://links.lww.com/DCR/A623 . Abstract : Supplemental Digital Content is available in the text.